Testing and Measurement on students' intention to use mobile learning based on UTAUT model - Tang, Weike; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2024)
The widely use of communication technologies and wireless network has changed people's lives in many aspects. In the current information age, traditional teaching can no longer meet the needs of students. The rapid development of wireless network provides a foundation for the advancement of mobile learning. This paper aims to build a tool to test the reliability and validity of the conceptual framework of factors affecting students' intention to use mobile learning in higher vocational colleges. The paper adopts the extended UTAUT model, including self-efficacy, personal innovativeness, content quality, with 9 latent variables and 58 items. The paper uses a sample size of 30 to perform the pilot test. The findings show 2 items have been modified and 1 item should be removed to get the better reliability and validity.
Keywords: items; mobile learning; observed variables; reliability; UTAUT; validity